An overview of the Onthophagini from the Arabian Peninsula (Coleoptera: Scarabaeoidea: Scarabaeidae) - Ziani, Stefano; Abdel-Dayem, Mahmoud Saleh; Aldhafer, Hathal Mohammed; Barbero, Enrico (Zootaxa, 2019)
The onthophagine fauna of the Arabian Peninsula is reviewed. New data from public and private collections are given. The total number of Onthophagini known from the Peninsula now stands at 30 species, without taking into account dubious records, belonging to seven genera. Of these 30 species, three (Onthophagus aethiopicus d’Orbigny, 1902, O. falsus Gillet, 1925 and O. frontalis Raffray, 1877) are reported for the first time from the Arabian Peninsula, six species (Digitonthophagus eucatta Génier in Génier & Moretto, 2017, Onthophagus aethiopicus d’Orbigny, 1902, O. brittoni Paulian, 1948, O. falsus Gillet, 1925, O. rugulipennis Fairmaire, 1887, and O. trapezicornis d’Orbigny, 1902) are new records from Saudi Arabia, three (D. eucatta, O. aethiopicus and O. frontalis) are new from Yemen and five (O. bicolor Raffray, 1877, O. latipennis d’Orbigny, 1898, O. nitidulus Klug, 1856, O. quadriarmatus Fairmaire 1892 and O. sellatus Klug, 1845) are new from Oman. Furthermore, Onthophagus infuscatus Klug, 1845 is recorded from Djibouti for the first time. For all the treated species a general distribution, literature citations and eventual unpublished records are provided. A new synonymy (Onthophagus saudiensis Frey, 1962 under O. sticticus Harold, 1867) is proposed. Most of the species were recorded from locations in southern Saudi Arabia, Oman and Yemen, south Tropic of Cancer. Yemen and Saudi Arabia have the highest species numbers, hosting the richest fauna with 24 and 23 species, respectively. The majority of the Onthophagini fauna (73.33 %) has Afrotropical and Afrotropical-Palaearctic affinities, while the Palaearctic and Oriental-Palaearctic species are both represented by 6.66 %. The four Arabian endemisms represent the 13.33 % of the whole fauna. Lastly, a dichotomous key for the identification of Arabian onthophagine species is provided and a redescription of Onthophagus brittoni is supplied.